Combined simultaneous enzymatic saccharification and comminution (SESC) and anaerobic digestion for sustainable biomethane generation from wood lignocellulose and the biochemical characterization of residual sludge solid. (March 2020) - Navarro, Ronald R.; Otsuka, Yuichiro; Matsuo, Kenji; Sasaki, Kei; Sasaki, Ken; Hori, Tomoyuki; Habe, Hiroshi; Nakamura, Masaya; Nakashimada, Yutaka; Kimbara, Kazuhide; Kato, Junichi
Graphical abstract: Combined SESC and anaerobic digestion of wood lignocellulose produce directly burnable biogas and natural lignin-rich precipitate. Highlights: SESC is effective for large-scale anaerobic digestion of wood lignocellulose. Anaerobic digestion of SESC slurry yielded 224 L methane/kg cedar. 16S rRNA analysis established the presence of relevant microbial sludge community. Natural lignin is an important by-product of combined SESC and anaerobic digestion. Abstract: Simultaneous enzymatic saccharification and comminution (SESC) was used for large-scale anaerobic digestion of wood lignocellulose to generate methane and unmodified lignin. During SESC, 10% aqueous mixture of powdered debarked wood from various species was subjected to bead milling with hydrolytic enzymes to generate particles below 1 μm. This slurry was directly used as a cosubstrate for anaerobic digestion in a 500 L stirred-tank reactor. Temperature and hydraulic retention time (HRT) were maintained at 50 °C and 30 days, respectively. At stable operation periods, an average yield of 224 L of methane per kg of cedar was attained. Comparable yields were achieved with red pine, elm, oak, and cedar bark. High-throughput microbial analysis established the presence of a relevant community to support the elevated level of methane production. The stability of the unmodified lignin in anaerobic digestion was also confirmed, allowing for its recovery as an important by-product.